2021
DOI: 10.1016/j.ijid.2020.11.170
|View full text |Cite
|
Sign up to set email alerts
|

A novel use of telemedicine during the COVID-19 pandemic

Abstract: Please cite this article as: { doi: https://doi.org/ This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…Their most important experiences significantly led to the recognition of various issues related to telehealth implementation, including (1) treatment initiation and patient examination; (2) telehealth visit set-up and structure while maintaining patient privacy; (3) reimbursements and billing considerations; (4) tele-visit limitations and services which do not meet the care needs of patients; and (5) optimisation of the tele-visit. As presented in [ 38 ], a telehealth system was implemented in a healthcare hospital to protect patients from COVID-19 transmission and manage patients infected with COVID-19. The implemented system was assessed by an expert team.…”
Section: Taxonomymentioning
confidence: 99%
“…Their most important experiences significantly led to the recognition of various issues related to telehealth implementation, including (1) treatment initiation and patient examination; (2) telehealth visit set-up and structure while maintaining patient privacy; (3) reimbursements and billing considerations; (4) tele-visit limitations and services which do not meet the care needs of patients; and (5) optimisation of the tele-visit. As presented in [ 38 ], a telehealth system was implemented in a healthcare hospital to protect patients from COVID-19 transmission and manage patients infected with COVID-19. The implemented system was assessed by an expert team.…”
Section: Taxonomymentioning
confidence: 99%
“…A team of local experts in Malta developed a telemedicine hub that included data about the newly diagnosed COVID-19 patients and coordinated medical assessment and management for those patients. During the early months of the COVID-19 pandemic, this hub safely managed 91% of COVID-19 patients in the country [23]. The University Hospital of Zurich implemented medical chatbots to offer early diagnosis, treatment, and medical information for remotely situated patients with dermatological conditions [24].…”
Section: Examples Of Telemedicine During the Covid-19 Pandemic Worldwidementioning
confidence: 99%
“…[7][8][9][10][11] Telemedicine has been widely used in the COVID-19 epidemic and has achieved good clinical effects. [12][13][14] WeChat (a platform for information conversations) is the most widely used social software in China, with more than 1 billion people using WeChat at least once a day. 15 It has been reported that WeChat can be used as a telemedicine model for the monitoring, prevention, and health management of diseases, such as infertility, chronic diseases, and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%